Arteriocolonic fistula of inferior mesenteric artery aneurysm: A case with lower gastrointestinal and intra-abdominal hemorrhage. Issue 3 (March 2023) - Li, Honghai; Yu, Zunfang; Wang, JinDao; Zhang, Zhenxing; Zhang, Guolin; Lu, Zengxin; Lv, Jieqing; Tao, Feng; Jin, Qijing
Abstract: Introduction: Arteriocolonic fistula of Inferior Mesenteric Artery Aneurysm (IMAA) refers to a spontaneous formation of pathological communication between the artery and the adjacent gastrointestinal tract. It is a rare, life-threatening condition primarily manifesting as abdominal pain, gastrointestinal bleeding, abdominal pulsating masses. However, its clinical manifestations are usually atypical with a difficult diagnosis and treatment. Case presentation: We report a rare case of a 50-year-old male with a hemorrhagic shock due to primary arteriocolonic fistula of IMAA. Instead of sigmoidectomy, super selective transcatheter arterial embolization (TAE) was performed after diagnostic angiography. Postoperatively, dynamic contrast-enhanced abdominal computed tomography (CT) demonstrated no recanalization of the aneurysm, absence of abnormal collateral vessels, no active hemorrhage. The patient was discharged uneventfully after 2 weeks without abdominal pain or tension. Discussion: Colorectal tumor rupture is a major cause of lower gastrointestinal bleeding (LGIB), with IMAA being an uncommon etiology. Because of the high mortality of explorative laparotomy with an unclear bleeding site, diagnostic angiography and therapeutic TAE are viable options for diagnosing hemodynamic instability. Conclusion: Arteriocolonic fistulas commonly occur secondary to a pseudoaneurysm formed at the anastomosis of the transplanted blood vessel after an artery surgery, which ruptures and penetrates into the intestine. We reported a unique case of primary arteriocolonic fistula of IMAA: aneurysm rupture and bleeding from the abdomen into the hematochezia. After multidisciplinary consultations, our patient obtained the best outcome using the most minimally invasive surgical methods. With an abdominal artery aneurysm presenting with colorectal hemorrhage, arteriocolonic fistula of IMAA should be suspected.